1985
DOI: 10.1007/bf00589248
|View full text |Cite
|
Sign up to set email alerts
|

Influences of endurance training on the ultrastructural composition of the different muscle fiber types in humans

Abstract: To investigate changes in the ultrastructure of the different muscle fiber types induced by endurance training ten sedentary subjects (five women and five men) were exercised on bicycle ergometers 5 times a week for 30 min. After 6 weeks of training there were significant changes in VO2max (+14%), in the percentage of type I (+12%) and type IIB fibers (-24%) as well as in the volume densities of mitochondria. The latter increased 35% in type I, 55% in type IIA and 35% in type IIB fibers. The relative increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
239
5
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(279 citation statements)
references
References 32 publications
26
239
5
9
Order By: Relevance
“…In contrast, significantly less H ϩ transporter activation was found in mitochondria from the low respiration group. Fatty acid activation of the uncoupling protein 3 and adenine nucleotide translocator could also underlie the increased respiration and uncoupling in TA vs. FDI found in this study because higher intracellular lipid levels are reported in type I fibers of human muscle (32).…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, significantly less H ϩ transporter activation was found in mitochondria from the low respiration group. Fatty acid activation of the uncoupling protein 3 and adenine nucleotide translocator could also underlie the increased respiration and uncoupling in TA vs. FDI found in this study because higher intracellular lipid levels are reported in type I fibers of human muscle (32).…”
Section: Discussionmentioning
confidence: 68%
“…CS is involved in oxidative ATP production and is found in direct proportion to muscle mitochondrial content [30,31]. Kim et al [32] showed that CS activity was significantly reduced in the vastus lateralis of obese subjects, suggesting that the low mitochondrial content in the skeletal muscle of these subjects contributed to their decrease in muscle oxidative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, muscle hypertrophy by cycle training is frequently observed when cycle training has been performed for relatively long periods (24,58,62). Thus, it is plausible that cycle training does not increase muscle size during short periods (34,35) but that cycle training requires relatively long periods to induce significant muscle hypertrophy (5,58).…”
mentioning
confidence: 99%